Pengaruh Kepemimpinan Kepala Sekolah Dan Motivasi Kerja Terhadap Kepuasan Kerja Di SMK N 2 Prabumulih - Dwi Wulan Sari; Nur Ahyani; Missriani, Missriani (CV. Ulil Albab Corp, 2024)
This research aims to analyze the influence of the principal's leadership and work motivation on job satisfaction at SMK Negeri 2 Prabumulih. This research uses a quantitative approach with survey methods. Data was collected through questionnaires distributed to 50 teachers at SMK Negeri 2 Prabumulih. Data analysis was carried out using multiple regression techniques to test the influence of the independent variables (school principal leadership and work motivation) on the dependent variable (job satisfaction). The research results show that the principal's leadership has a significant positive influence on job satisfaction, as well as work motivation which also has a positive influence on job satisfaction. Simultaneously, these two variables make a significant contribution to the level of job satisfaction at the school. This research provides recommendations so that school principals can pay more attention to the leadership style applied and increase teacher work motivation in order to increase overall job satisfaction.